2019
DOI: 10.3389/fgene.2019.00366
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble Strategy to Predict Prognosis in Ovarian Cancer Based on Gene Modules

Abstract: Due to the high heterogeneity and complexity of cancer, it is still a challenge to predict the prognosis of cancer patients. In this work, we used a clustering algorithm to divide patients into different subtypes in order to reduce the heterogeneity of the cancer patients in each subtype. Based on the hypothesis that the gene co-expression network may reveal relationships among genes, some communities in the network could influence the prognosis of cancer patients and all the prognosis-related communities coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Generally, there are two approaches to determine the value of k; one is to directly set it as the true number of clusters (Yu et al, 2018;Zhao et al, 2021;Liu et al, 2022;Wu and Ma, 2022); The other approach is applicable to the case where the true number of clusters is unknown, in which the variation range of k is determined firstly, and the k corresponding to the optimal value of an index (Silhouette index, Dunn index, Davies-Bouldin index, etc.) can be chosen as the optimal number of clusters (Gao et al, 2019;Acharya et al, 2020;López-Cortés et al, 2020;Zhang et al, 2022). In this paper, we adopt the first approach, and the number of clusters k is selected according to Table 1.…”
Section: Model Evaluation Criteria and Parameter Assignmentmentioning
confidence: 99%
“…Generally, there are two approaches to determine the value of k; one is to directly set it as the true number of clusters (Yu et al, 2018;Zhao et al, 2021;Liu et al, 2022;Wu and Ma, 2022); The other approach is applicable to the case where the true number of clusters is unknown, in which the variation range of k is determined firstly, and the k corresponding to the optimal value of an index (Silhouette index, Dunn index, Davies-Bouldin index, etc.) can be chosen as the optimal number of clusters (Gao et al, 2019;Acharya et al, 2020;López-Cortés et al, 2020;Zhang et al, 2022). In this paper, we adopt the first approach, and the number of clusters k is selected according to Table 1.…”
Section: Model Evaluation Criteria and Parameter Assignmentmentioning
confidence: 99%
“…Epigenetic changes are integral to all aspects of cancer genomics, such as DNA methylation, which is among the common epigenetic mechanisms involved in the formation and development of cancer [11,12]. A large body of studies has shown that aberrant methylation of global DNA or specific genes may affect the progression [13] and prognosis of ovarian cancer [14], but the mechanisms for the aberrant DNA methylations to be involved in ovarian cancer remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%